Oppositional Slime Mould Algorithm: Development and application for designing demand side management controller. (15th March 2023) - Sharma, Ankit Kumar; Saxena, Akash; Palwalia, D.K.
Abstract: In recent years, application of several metaheuristic optimization algorithms have been reported. Their flexibility and adaptive structure make them compatible for real engineering design problems. The ability of the optimization algorithm for solving any design problem depends upon the balance between exploration and exploitation phase of the algorithm. These phases are determined by inherent mathematical equations. For making any algorithm compatible for engineering design tasks, certain modifications are required. In this work, we apply two modifications namely (opposition theory and sine cosine based position update mechanism for enhancing exploration and exploitation virtues of recently introduced Slime Mould Algorithm (SMA). Further, the suitability of designing a Demand Side Management Controller by proposed algorithm is explored with the help of standard mathematical analysis and bench marking procedures. Comparison of DSM controllers based on different algorithms has also been evaluated. The results reveal that proposed modifications enhances the optimization capability of SMA.